Shoulder proprioception is not related to throwing speed or accuracy in elite adolescent male baseball players - Freeston, J.; Adams, R. D.; Kieron, R. (The Journal of Strength and Conditioning Research, 2015)
Understanding factors that influence throwing speed and accuracy is critical to performance in baseball. Shoulder proprioception has been implicated in the injury risk of throwing athletes, but no such link has been established with performance outcomes. The purpose of this study was to describe any relationship between shoulder proprioception acuity and throwing speed or accuracy. Twenty healthy elite adolescent male baseball players (age, 19.6 ± 2.6 years), who had represented the state of New South Wales in the past 18 months, were assessed for bilateral active shoulder proprioception (shoulder rotation in 90° of arm abduction moving toward external rotation using the active movement extent discrimination apparatus), maximal throwing speed (MTS, meters per second measured via a radar gun), and accuracy (total error in centimeters determined by video analysis) at 80 and 100% of MTS. Although proprioception in the dominant and nondominant arms was significantly correlated with each other (r = 0.54, p < 0.01), no relationship was found between shoulder proprioception and performance. Shoulder proprioception was not a significant determinant of throwing performance such that high levels of speed and accuracy were achieved without a high degree of proprioception. There is no evidence to suggest therefore that this particular method of shoulder proprioception measurement should be implemented in clinical practice. Consequently, clinicians are encouraged to consider proprioception throughout the entire kinetic chain rather than the shoulder joint in isolation as a determining factor of performance in throwing athletes.